Carbon isotope and soluble metabolites reflect physiological status among contrasting faba bean genotypes in response to water deficit - Muktadir, Md Abdul; Merchant, Andrew; Sadeque, Abdus; Tanveer, Mohsin; Adhikari, Kedar Nath; Huang, Liping (Frontiers in Plant Science, 2022)
Identification and validation of biomarkers and bioindicators to select genotypes with superior tolerance to water deficit (WD) under field conditions are paramount to plant breeding programs. However, the co-occurrence of different abiotic stresses such as WD, heat and radiation make it difficult to develop generalized protocols to monitor the physiological health of the plant system. The study assessed the most abundant carbohydrates and sugar alcohols in five faba bean (Vicia faba) genotypes under field conditions and the abundance of naturally occurring carbon isotopes in bulk leaf material to predict water use efficiency (WUE). Plant water status and biomass accumulation was also assessed. Among the accumulated sugars, inter-specific variation in glucose was most prevalent and found higher concentration (8.52 mg g-1 leaf) in rainfed trial. Myo - Inositol concentrations followed that of glucose accumulation in that the rainfed trial had higher amounts compared to the irrigated trial. WUE calculated from carbon isotope abundance was consistently offset with measured WUE from measurements of leaf gas exchange. All genotypes demonstrated significant relationships between predicted and measured WUE (P< 0.05) apart from control variety PBA Warda. Thus, bulk leaf-level carbon isotope abundance can be used to calculate WUE and used as an effective selection criterion for improving WUE in faba bean breeding programs under field conditions.